Prognostic role of KRAS, NRAS, BRAF and PIK3CA mutations in advanced colorectal cancer. (February 2015) - Foltran, Luisa; Maglio, Giovanna De; Pella, Nicoletta; Ermacora, Paola; Aprile, Giuseppe; Masiero, Elena; Giovannoni, Mariella; Iaiza, Emiliana; Cardellino, Giovanni Gerardo; Lutrino, Stefania Eufemia; Mazzer, Micol; Giangreco, Manuela; et al.
ABSTRACT : Aim : To explore the prognostic value of extended mutational profiling for metastatic colorectal cancer (mCRC).Materials & methods : We retrospectively reviewed survival results of 194 mCRC patients that were assigned to four molecular subgroups: BRAF mutated; KRAS mutated codons 12-13 only; any of KRAS codons 61-146, PIK3CA or NRAS mutations and all wild-type. Point mutations were investigated by pyrosequencing.Results: BRAF (5.2%) and KRAS 12-13 (31.9%) mutations were associated with poorer survival (HR 2.8 and 1.76, respectively). Presenting with right-sided colon cancer, not resected primary tumor, WBC >10 × 10 9 /l, receiving less chemotherapy or no bevacizumab were all associated with inferior outcome. The all-wild-type subgroup (39.2%) reported the longest survival.Conclusion : Extended mutational profile combined with clinical factors may impact on survival in mCRC.